On Emily Paul on Brian Leftow - Collier, Matthew James (TheoLogica, 2019)
Emily Paul has recently argued that Brian Leftow's account of why the import of God's becoming Incarnate is not temporal but modal fails. She argues that Leftow's required modal variation is not satisfied. That is, we do not have the required variation across logical space concerning the Incarnation. Paul examines her argument on two possible worlds theories: theistic ersatzism and (what I call) Lewisian theism. She thinks that both possible worlds theories face difficulties. I argue that Paul fails to provide a compelling argument against Leftow because, firstly, her defence of one her premises fails, and, secondly, she misjudges what is required for some of Leftow's claims to be true. I also argue that some of the problematic consequences that Paul raises for theistic ersatzism and Lewisian theism either are not problematic or can be avoided.